Description and analysis of the white shrimp (Litopenaeus Schmitti) fisheries in Pearl Lagoon, Atlantic Coast of Nicaragua, with focus on the gear selectivity in the artesanal fleets / Clarece Oliver Gonzáles Colindres - González Colindres, Clarence Oliver (2006)
Fishing continues to be the mam source of income in the Pearl Lagoon Basin in Nicaragua. Currently the fishermen in the area have expressed growing condemn about the shrimp's stocks. Over the past years it has become increasingly clear that the fish and shrimp stocks are being exhausted, severely over-fished and experiencing a serious decline. This thesis examines the catch compositions (shrimps and by-catch) of three mesh sizes of the Cast net gear employed in the fishery through sampling during the months of July and August, as well as analyzes the current situation of the shrimp inside the lagoon through primary (interviews) and secondary (books, joumals, articles, reports, etc.) data. The data samples of the experiment with the different mesh sizes identified in the thesis were analyzed using standard software applying a trouser trawl method to determine the selectivity curve. Single factor ANOV A tests. where use to distinguish significant differences between lengths. Significant differences were also tested combining the three different mesh sizes applying the SPSS turkey multi comparison computer program model. The findings were discussed and compared with a previous selectivity study accomplished in the lagoon; the thesis concludes that gears with ½ inch mesh size were vulnerable to the species during these months by retaining low weight and smallef length shrimp compositions (70% of the capture is between 5 and 8 cm total length). 1 inch and 1 ½ inch mesh sizes showed a general improvement in the selective performance of the gear (approximately 90% of the captured shrimps were between 11 and 14 cm); the main secondary findings show that local people are employing small gear mesh sizes in the lagoon, especially those whose sustainability livelihoods are significantly threatened with very few opportunities of survival; most obvious those who live in the more remote areas